Ectopic expression of RAD52 and dn53BP1 improves homology-directed repair during CRISPR–Cas9 genome editing. (November 2017) - Paulsen, Bruna; Mandal, Pankaj; Frock, Richard; Boyraz, Baris; Yadav, Rachita; Upadhyayula, Srigokul; Gutierrez-Martinez, Paula; Ebina, Wataru; Fasth, Anders; Kirchhausen, Tomas; Talkowski, Michael; Agarwal, Suneet; et al.
Abstract Gene disruption by clustered regularly interspaced short palindromic repeats (CRISPR)–CRISPR-associated protein 9 (Cas9) is highly efficient and relies on the error-prone non-homologous end-joining pathway. Conversely, precise gene editing requires homology-directed repair (HDR), which occurs at a lower frequency than non-homologous end-joining in mammalian cells. Here, by testing whether manipulation of DNA repair factors improves HDR efficacy, we show that transient ectopic co-expression of RAD52 and a dominant-negative form of tumour protein p53-binding protein 1 (dn53BP1) synergize to enable efficient HDR using a single-stranded oligonucleotide DNA donor template at multiple loci in human cells, including patient-derived induced pluripotent stem cells. Co-expression of RAD52 and dn53BP1 improves multiplexed HDR-mediated editing, whereas expression of RAD52 alone enhances HDR with Cas9 nickase. Our data show that the frequency of non-homologous end-joining-mediated double-strand break repair in the presence of these two factors is not suppressed and suggest that dn53BP1 competitively antagonizes 53BP1 to augment HDR in combination with RAD52. Importantly, co-expression of RAD52 and dn53BP1 does not alter Cas9 off-target activity. These findings support the use of RAD52 and dn53BP1 co-expression to overcome bottlenecks that limit HDR in precision genome editing. The expression of two specific DNA-repair factors promotes homology-directed repair and enhances the precision of CRISPR–Cas9 gene editing at multiple loci in ﻿hu﻿man cells﻿, including﻿ patient-derived induced pluripotent stem cells.